The Effect of PBL Model on Students' Mathematical Problem-Solving Ability Based on HOTS Questions - Rohyati Rohyati; Joko Purwanto (AlphaMath : Journal of Mathematics Education, 2023)
Problem-solving is a practical approach to stimulating higher-order thinking skills. The strategy that can be used is to apply a learning model, one of which is Problem-Based Learning (PBL). This study aimed to determine the effect of PBL on the ability to solve mathematical problems based on higher-order thinking Skills (HOTS) at SMA Negeri 1 Baturraden. This study used a quantitative approach with a quasi-experimental method. The research design used was post-test-only. The research sample was taken using the cluster random sampling technique. The research instrument used was a mathematical problem-solving ability test based on HOTS questions. Data analysis was conducted using an independent sample t-test. The results showed that students who participated in PBL learning had better mathematical problem-solving skills based on HOTS questions than students who participated in conventional learning. In PBL learning, students will be able to (1) Students better understand the concept; (2) in learning activities, students are actively involved; (3) the learning process is more meaningful; (4) Can motivate and increase student interest in the material being studied; (5) Can emphasize positive social attitudes towards other students, such as accepting other people's opinions; (6) There is interaction between learners and their friends to achieve learning completeness; (7) Able to foster student creativity both individually and in groups.